Islamization in Bengal - Ashraf Uz Zaman (Indonesian Journal of Islamization Studies, 2024)
This article investigates the historical and socio-cultural dimensions of Islamization in Bengal, shedding light on the processes that contributed to the region's Islamic transformation. Utilizing a comprehensive approach that incorporates historical records, literary sources, and indigenous narratives, the study examines pivotal moments and factors influencing the adoption and evolution of Islamic practices in Bengal. By delving into the intricate tapestry of Bengal's history, this research seeks to provide a nuanced understanding of the complex interplay between local traditions, external influences, and the emergence of Islam as a prominent cultural and religious force in the region.